Pion: a construção de um portal para os professores de Física - Escanhoela, Felipe Moron (Universidade Federal de São Carlos, 2011)
Pion, the web portal of the Brazilian Physical Society (SBF) for physics teaching and dissemination, provides to the public at large a collection of learning objects such as videos, photos, illustrations, didactic simulations, texts and other resources related to physics and its teaching. This work is an account of the web portal development and the achievement of an evaluation research on its usability and use by the public. An online form with multiplechoice questions and one open question were sent by e-mail to all registered users of the portal. The closed responses were evaluated in line with a Likert scale model and the views expressed in the open question were classified according to afterwards created categories. The research led to the conclusion that Pion is well structured concerning its usability and fulfills the role of assisting the teacher in their search for relevant information to teaching practice, although it still needs for improvement in aspects related to interaction with the public and the interactivity in general.
Keywords: Física - estudo e ensino; Portais da Web; Educação; Ensino; Informática; Objeto de aprendizagem; Portal de educação; Ensino de física; Informática na educação; Professor de física; Objeto de aprendizagem; Usabilidade de portal de internet; Education web portal; Physics teaching; Informatics in education; Teacher of physics; Learning objects; Web portal usability; CIENCIAS EXATAS E DA TERRA::FISICA